2019
DOI: 10.3389/fpsyg.2019.02243
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Language Skills: A Comparison of Children With Cochlear Implants and Children Without Hearing Loss

Abstract: Pragmatic language ability refers to the ability to use language in a social context. It has been found to be correlated with success in general education for deaf and hard of hearing children. It is therefore of great importance to study why deaf and hard of hearing children often perform more poorly than their hearing peers on tests measuring pragmatic language ability. In the current study the Pragmatics Profile questionnaire from the CELF-IV battery was used to measure pragmatic language ability in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 50 publications
3
30
0
1
Order By: Relevance
“…The results from the non-verbal intelligence task have been reported in another study about pragmatic language ability (Socher et al, 2019). Missing data and differences in matching procedure led to the differences in terms of the sample include here and in the study about pragmatic language ability.…”
Section: Participantsmentioning
confidence: 75%
“…The results from the non-verbal intelligence task have been reported in another study about pragmatic language ability (Socher et al, 2019). Missing data and differences in matching procedure led to the differences in terms of the sample include here and in the study about pragmatic language ability.…”
Section: Participantsmentioning
confidence: 75%
“…The testing was part of two larger research projects (Socher, 2020;Wass et al, 2019) and the children were tested on more tasks than are reported here. The results from the verbal fluency task from the project by Socher (2020) have previously been used in another paper on pragmatic language ability (Socher et al, 2019). The results from the verbal fluency task from the project by Wass et al have previously been reported in an article on orthographic learning (Wass et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The data collection for the children with TD (Ref: 2015/308-31) and adolescents with ID (Ref: 2017/139-31) was approved by the local Research Ethics Review Committee in Linköping. The results from the semantic verbal fluency test of the TD group have been reported in another study about pragmatic language ability [27]. The result from the semantic verbal fluency data of the ID group is used in two pre-registered studies investigating reading ability in adolescents with ID [26].…”
Section: Participants and Recruitmentmentioning
confidence: 99%